Trichophyton rubrum inhibits Candida albicans filamentation and its gene expression when grown in biofilms in vitro - Bila, Níura Madalena [UNESP]; Vaso, Carolina Orlando [UNESP]; Belizário, Jenyffie Araújo [UNESP]; Santoni Biasioli, Mariana M. [UNESP]; Fusco-Almeida, Ana Marisa [UNESP]; Martinez, Luis R.; Costa-Orlandi, Caroline Barcelos [UNESP]; Mendes-Giannini, Maria José Soares [UNESP] (FapUNIFESP (SciELO), 2025)
Dermatomycoses are caused by various fungi, including dermatophytes and Candida species, which are the most prevalent in isolated or associated forms. A great number of virulence factors expressed by these fungi are important for infection, and biofilm formation leads to the persistence of these infections. This work aimed to evaluate the dynamics of Candida albicans filamentation genes in biofilms formed by Candida albicans and Trichophyton rubrum. The effect of the supernatants on the biofilms was assessed by XTT reduction assay, confocal microscopy, and gene expression profile analysis by real time-PCR. The supernatants did not reduce the metabolic activities or damage the topography of the monospecies biofilms but caused a reduction in their thickness. The filamentation of C. albicans was inhibited when both fungi were cultivated directly. The filamentation genes studied (CPH1, HWP1, and EFG1) were negatively modulated in C. albicans. Our findings suggest that the antagonistic relationship shown by T. rubrum against C. albicans may be attributed to alterations of C. albicans filamentous genes.
Keywords: Antagonism; dermatomycoses; gene expression; virulence factors; filamentation; mixed biofilms